Edukasi Peningkatan Pengetahuan Masyarakat dalam Menerapkan Konsep 3R, Pencegahan Penyakit Tidak Menular, Pintar dengan Obat dan PHBS di Nagari Paninggahan - Sri Siswati; Ghina Azaria Shalda; Seftiando Tehira Ago Vijay; Devina Rahmadayanthi Suhendri; Natashya Aurellia R; Jennifer Jennifer; Mawazinal Khisti; Azarine Sidqi Najla; Gusrina Fauziah (Warta Pengabdian Andalas, 2022)
Environmental factors primarily influence the degree of public health. However, what is happening in today's society in improving the degree of health is even higher in health services. Many people receive curative treatment in health facilities but pay little attention to personal and environmental hygiene. The problems in Nagari Paninggahan are the need for more knowledge and awareness of the Paninggahan community in waste management, non-communicable diseases, rational use of drugs, and personal hygiene. This activity aims to increase public knowledge and awareness to improve the health status of the Paninggahan community. This activity was carried out using health promotion methods and practices and through leaflets. The results were that people could use used goods to make new, more valuable goods, understand that diseases such as hypertension must be appropriately handled with routine checks, know how to use the right medicines and practice proper hand washing to avoid various diseases. This activity hopes to increase public knowledge and awareness to avoid disease and improve the health status of the Paninggahan community.